PHYSIOTHERAPY TECHNIQUES MOST USED IN TOTAL KNEE ARTHROPLASTY AND QUALITY OF THEIR EVIDENCE: A SYSTEMATIC REVIEW 2010-2020 - Vargas Martínez, Brenda Pamela (2022)
Abstract: Total Knee Arthroplasty is a surgery that replaces the damaged joint -patella, distal articular surface of the femur and proximal articular surface of the tibia- with artificial parts known as prostheses. This surgery requires a parallel physiotherapeutic approach that allows the recovery of greater functional independence. Given the variety of physiotherapeutic interventions that can be implemented, it is important to identify those that have the most scientific evidence. The objective of the research carried out was to identify the most used physiotherapeutic techniques in Total Knee Arthroplasty and the quality of their evidence, through a systematic review 2010-2020. A systematic review was carried out based on the specifications stipulated in a clinical care guide. Forty scientific articles were reviewed in which four physiotherapeutic interventions were identified: electrotherapeutic modalities, physical agents, therapeutic exercise, passive mobilizations and other physiotherapeutic interventions. In addition, it was obtained that 27.5% of the articles presented quality of ++++, 42.5% quality of +++, 17.5% quality ++ and 12.5% with quality of +. In conclusion, it is highlighted that a little less than half of the studies obtained quality of +++ or moderate quality, which could be related to the lack of rigor in the research methodologies of the studies or the scarcity of research in the area. Both situations highlight the recent growth of the career in relation to research activity and the need to direct it towards evidence-based care.   Key words: Physical therapy modalities, Evidence based practice, Arthroplasty-replacement knee, Rehabilitation. Source: DeCS/MeSH.